Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ejoc.202100074
|View full text |Cite
|
Sign up to set email alerts
|

Late‐stage Rh(II)‐catalyzed Nitrene Transfer for the Synthesis of Guaianolide Analogs with Enhanced Antiproliferative Activity

Abstract: A set of new guaianolide derivatives (1–9) was obtained from ludartin, achalensolide, and 11,13‐dihydroachalensolide by application of catalytic nitrene transfer reactions. Intermolecular nitrene C(sp3)−H insertions led to the amination of C‐1, C‐2, and C‐10 positions, while alkene aziridination was also observed under these reaction conditions. The antiproliferative activity of natural compounds and their derivatives was evaluated against a panel of human solid tumor cell lines. The results show that an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…21 Inspired by these studies, Castro et al reported one of the early examples of C-H amination of natural products via regio-and stereo-selective Rh(II)catalyzed C-H nitrene insertion 22 on the moderately active sesquiterpene lactone ludartin (1, GI 50 10-20 mM), with full preservation of its a-methylene-g-lactone pharmacophore unit (Scheme 1). 23 True to expectations, the resulting sulfamates 2a,b showed 410 fold increase in potency against a number of human cancer cell lines, with 420-fold selectivity over the human fibroblast cell line BJ-hTERT.…”
Section: C-h Aminationmentioning
confidence: 52%
See 1 more Smart Citation
“…21 Inspired by these studies, Castro et al reported one of the early examples of C-H amination of natural products via regio-and stereo-selective Rh(II)catalyzed C-H nitrene insertion 22 on the moderately active sesquiterpene lactone ludartin (1, GI 50 10-20 mM), with full preservation of its a-methylene-g-lactone pharmacophore unit (Scheme 1). 23 True to expectations, the resulting sulfamates 2a,b showed 410 fold increase in potency against a number of human cancer cell lines, with 420-fold selectivity over the human fibroblast cell line BJ-hTERT.…”
Section: C-h Aminationmentioning
confidence: 52%
“…For example, C-H oxidation of the potent antileukemic sesquiterpene parthenolide ( 14), employing two mutated FL#62 variants, namely XII-F12 and XII-D8 (or VII-H11), led to preferential formation of the C-H hydroxylated derivatives 16 and 17, respectively, with 480% regioselectivity and high turnover numbers (TTN 4 500) (Scheme 5). 29a The latter were then used as templates to prepare small libraries of benzoates (18,19), 29a carbamates (20, 21) and ethers (22,23) (Scheme 6). 29b,c While the lipophilic CF 3 -substituted benzoates (18a-c/19a-c) led to a 3 fold increase in anti-leukemic potency on AML 123009, the corresponding carbamates (20a, 21a) displayed submicromolar potency on solid tumor cell lines (HeLa and SK-M-NC), unravelling a hitherto unknown biological profile of parthenolides (see Table , Scheme 6).…”
Section: C-h Hydroxylationmentioning
confidence: 99%